2007
DOI: 10.1002/ijc.22933
|View full text |Cite
|
Sign up to set email alerts
|

Aldo–keto reductase family 1 B10 gene silencing results in growth inhibition of colorectal cancer cells: Implication for cancer intervention

Abstract: Aldo-keto reductase family 1 B10 (AKR1B10), a member of aldoketo reductase superfamily, is overexpressed in human hepatocellular carcinoma, lung squamous cell carcinoma and lung adenocarcinoma. Our previous study had demonstrated that the ectopic expression of AKR1B10 in 293T cells promotes cell proliferation. To evaluate its potential as a target for cancer intervention, in the current study we knocked down AKR1B10 expression in HCT-8 cells derived from a colorectal carcinoma, using chemically synthesized sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
102
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 81 publications
(129 reference statements)
4
102
1
Order By: Relevance
“…The AKR1B10 protein is strongly overexpressed in lung and hepatic carcinomas (squamous cell and adenocarcinomas) (Fukumoto et al, 2005;Cao et al, 1998), as well as in colorectal and uterine cancers (Yoshitake et al, 2007). It has been shown that silencing of AKR1B10 gene using siRNA results in growth inhibition and reduced foci formation rate and colony size of colorectal cancer cells, indicating that AKR1B10 plays a critical role in cancer cell proliferation (Yan et al, 2007). The mitogenic role of AKR1B10 may be related to the depletion of retinoic acid (due to excessive AKR1B10 activity) and subsequent loss of cell differentiation and cancer development (Gallego et al, 2007).…”
Section: Akr1b10 -Small Intestine Aldose Reductasementioning
confidence: 99%
See 1 more Smart Citation
“…The AKR1B10 protein is strongly overexpressed in lung and hepatic carcinomas (squamous cell and adenocarcinomas) (Fukumoto et al, 2005;Cao et al, 1998), as well as in colorectal and uterine cancers (Yoshitake et al, 2007). It has been shown that silencing of AKR1B10 gene using siRNA results in growth inhibition and reduced foci formation rate and colony size of colorectal cancer cells, indicating that AKR1B10 plays a critical role in cancer cell proliferation (Yan et al, 2007). The mitogenic role of AKR1B10 may be related to the depletion of retinoic acid (due to excessive AKR1B10 activity) and subsequent loss of cell differentiation and cancer development (Gallego et al, 2007).…”
Section: Akr1b10 -Small Intestine Aldose Reductasementioning
confidence: 99%
“…The AKR1B10 gene has been found induced by cigarette smoke condensate in human oral cells (Nagaraj et al, 2006). Because the enzyme shows high catalytic activity with aldehydes in cigarette smoke such as acrolein and crotonaldehyde (Yan et al, 2007), it is likely that, like aldose reductase, AKR1B10 protective against electrophilic injury. In addition, AKR1B10 appears to regulate biosynthesis of fatty acids through association with a rate-limiting enzyme of de novo synthetic pathway acetyl-CoA carboxylase-α (Ma et al, 2008), however, the physiological significance of this role of AKR1B10 needs to be explored further.…”
Section: Akr1b10 -Small Intestine Aldose Reductasementioning
confidence: 99%
“…Thus, an increase in AKR1B10 activity seriously inhibits retinoic acid synthesis, which can be associated with subsequent loss of cell differentiation and cancer development (7). Recent work showed that down-regulation of the AKR1B10 gene using siRNA promoted cell death in colorectal cancer cells through enhanced cytotoxicity of reactive carbonyls produced from lipid peroxidation (8). In other studies, inhibition of AKR1B10 resulted in disruption of lipid synthesis, mitochondrial function and oxidative status, all of which are involved in important cell survival mechanisms (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…It requires, however, further mechanistic study because knowing the mechanism would allow the development of clinical drugs without unwanted side effects. Interestingly, AKR1B1 and AKR1B10 show about 71% homology in their amino acid sequences (15), and also show similar substrate specificity towards several endogenous substrates, such as retinals (2), phospholipid aldehydes (16), and acrolein (8). For this reason, selective ARIs might also be inhibitors for AKR1B10, resulting in inhibition in certain types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This protein is primarily expressed in the human colon and small intestine but overexpressed in breast cancer, hepatocellular carcinoma, non-small cell lung carcinoma, and cervical and endometrial cancers (1)(2)(3)(4). AKR1B10 may be implicated in cancer development and progression by activating procarcinogen polycyclic aromatic hydrocarbon in cigarette smoke and the environment (5), regulating cellular retinoic acid levels (6 -8), mediating fatty acid synthesis (9,10), and detoxifying cytotoxic carbonyl compounds (11)(12)(13)(14)(15)(16)(17) and therapeutic drugs (18,19). Recent studies have demonstrated that AKR1B10 expressed in the intestinal epithelium and cultured cancer cells is secreted through a lysosome-mediated nonclassical protein secretion pathway (20), indicating its detoxicating and/or paracrine role locally in the intestine and in distant organs.…”
mentioning
confidence: 99%